2021
DOI: 10.1002/emp2.12452
|View full text |Cite
|
Sign up to set email alerts
|

A case of SARS‐CoV‐2‐associated arthritis with detection of viral RNA in synovial fluid

Abstract: Severe acute respiratory distress syndrome‐coronavirus‐2 (SARS‐CoV‐2) provokes symptoms ranging from mild viral illness to a systemic inflammatory syndrome with multi‐organ failure and has been associated with cases of arthritis. We report a clinical case of SARS‐CoV‐2 associated arthritis in which analysis of synovial fluid detected SARS‐CoV‐2 ribonucleic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…Then we excluded 11 patients: 4 with a gout attack, 1 with established RA, 1 with isolated dactylitis, 1 patient who had already been investigated for arthritis before COVID-19 and 4 patients with back pain and sacroiliitis by MRI but with an age at onset > 45 years. Therefore, our review related to arthritis was based on 28 studies [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ] ( Supplementary file ). All included studies were published as full-text journal articles.…”
Section: Resultsmentioning
confidence: 99%
“…Then we excluded 11 patients: 4 with a gout attack, 1 with established RA, 1 with isolated dactylitis, 1 patient who had already been investigated for arthritis before COVID-19 and 4 patients with back pain and sacroiliitis by MRI but with an age at onset > 45 years. Therefore, our review related to arthritis was based on 28 studies [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ] ( Supplementary file ). All included studies were published as full-text journal articles.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies also showed no presence of SARS-CoV-2 in the joint of COVID-19 cadavers after analyzing the synovial fluid, synovial membrane, and bone via real-time polymerase chain reaction [ 31 ]. In contrast, one study of a non-hospitalized medium ill patient found traces of nucleic acids of SARS-CoV-2 in the joint [ 32 ]. In general, this points to a non-immediate role of SARS-CoV-2 in the onset of musculoskeletal changes after a SARS-CoV-2 infection.…”
Section: Covid-19 and Musculoskeletal Dysfunctionmentioning
confidence: 99%
“…Recent studies showed that only sporadically nucleic acids of SARS-CoV-2 could be found in the joint [ 31 , 32 ]. Therefore, it seems unlikely that SARS-CoV-2 will directly affect the joint tissue.…”
Section: Early Ageing Alterations In Endothelial and Adipose Tissue Of Covid-19 Patientsmentioning
confidence: 99%
“…The alternative is that it may be late-onset viral arthritis with actual invasion of the synovial space with the virus [ 78 ]. We could identify one study that reported the detection of SARS-CoV-2 RNA in a patient with wrist arthritis that had appeared 15 days after diarrhoea and upper respiratory tract symptoms [ 79 ]. However, other cases have not found such evidence [ 80 ].…”
Section: Current Definitions and Limitationsmentioning
confidence: 99%